Unsupervised Representation Learning Using Wasserstein Generative Adversarial Network - Iftakher Hasan Mohammed Tarek; Mohammed Mahmudur Rahman; Zulkifly Mohd Zaki (www.computingonline.net, 2024)
Indexed by Scopus